2019
DOI: 10.4101/jvwr.v12i1.7329
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality in Education: Focus on the Role of Emotions and Physiological Reactivity

Abstract: Cognitive and emotional dimensions are often linked to each other in learning experiences. Moreover, emotions and engagement can lead to better outcomes at the cognitive level. Previous research has indicated that virtual reality (VR) provides a feeling of presence and immersion, which can trigger emotionally engaging learning situations. In this study, we explore the opportunities and challenges related to the use of VR in an educational context. The focus of this article is threefold: First, we explore inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 32 publications
0
36
0
1
Order By: Relevance
“…After the students complete a learning activity, they usually receive a reward. -Virtual reality (VR) and Augmented reality (AR): Currently, they are the most popular training innovations [38]. Virtual reality has been around for a long time.…”
Section: Standards and Trends In E-learningmentioning
confidence: 99%
“…After the students complete a learning activity, they usually receive a reward. -Virtual reality (VR) and Augmented reality (AR): Currently, they are the most popular training innovations [38]. Virtual reality has been around for a long time.…”
Section: Standards and Trends In E-learningmentioning
confidence: 99%
“…Both measures suggested that working in small groups facilitated by the teacher was physiologically more alerting/engaging and meaningful than the lectures. Vesisenaho et al [13] reviewed the feasibility of studying learning experiences, specifically self-assessed experience of emotional involvement, in a virtual reality environment and of using (neuro)physiological measures in this context.…”
Section: Combining Learning Experiences and Physiologymentioning
confidence: 99%
“…However, there are some well-known variables that can be extracted from physiological measurements, and to some extent also from neurophysiological measures, that link with particular states, such as arousal, stress-level and vigilance [16], [17]. When these measures are integrated with experiential and cognitive measures, the complementary information across modalities can give meaningful and novel information of opportunities and challenges in learning situation (see [13]). However, systematic study of the reliability and usefulness of such measurements needs yet to be shown.…”
Section: Combining Learning Experiences and Physiologymentioning
confidence: 99%
“…The interactions can be almost real and physical when a person uses specific electronic tools installed with sensors (for example, helmet or gloves). A previous study [7][8][9][10] conducted on VR learning experiences among students, demonstrated a positive finding of VR simulation. It reflected in the improvements in prescribed structures of knowledge [11].…”
Section: Introductionmentioning
confidence: 99%